2001
DOI: 10.2174/1381612013398013
|View full text |Cite
|
Sign up to set email alerts
|

Type II Topoisomerases as Targets for Quinolone Antibacterials Turning Dr. Jekyll into Mr. Hyde

Abstract: Quinolones are a very important family of antibacterial agents that are widely prescribed for the treatment of infections in humans. Although the founding members of this drug class had little clinical impact, successive generations include the most active and broad spectrum oral antibacterials currently in use. In contrast to most other anti-infective drugs, quinolones do not kill bacteria by inhibiting a critical cellular process. Rather, they corrupt the activities of two essential enzymes, DNA gyrase and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
189
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(193 citation statements)
references
References 103 publications
3
189
0
1
Order By: Relevance
“…Interestingly, studies have shown that although quinolone agents target bacterial topoisomerase and gyrase, some quinolones also seem to interact with eukaryotic type II topoisomerase. 39,40 For example, ciprofloxacin has been shown to be a modest enhancer of DNA cleavage mediated by eukaryotic topoisomerase II. 40 Based on this, some quinolones have been tested for their efficacy as anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have shown that although quinolone agents target bacterial topoisomerase and gyrase, some quinolones also seem to interact with eukaryotic type II topoisomerase. 39,40 For example, ciprofloxacin has been shown to be a modest enhancer of DNA cleavage mediated by eukaryotic topoisomerase II. 40 Based on this, some quinolones have been tested for their efficacy as anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Quinolones, such as CP-115,953, are the only drugs that show high activity against eukaryotic and prokaryotic type II enzymes [101,[122][123][124][125]. While this last drug class has not yet been exploited to treat cancer, quinolones such as ciprofloxacin and levofloxacin that target bacterial type II topoisomerases are the most active and broad-spectrum oral antibacterials in clinical use [124,126,127].…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
“…While this last drug class has not yet been exploited to treat cancer, quinolones such as ciprofloxacin and levofloxacin that target bacterial type II topoisomerases are the most active and broad-spectrum oral antibacterials in clinical use [124,126,127].…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial fluoroquinolones have been found to be one of the fastest growing groups of drugs in recent years [5][6][7][8] . Quinolones are known for their antibacterial and antitumor activities through alteration of the normal functions of bacterial gyrase, and are found to be a topoisomerase II inhibitor in humans [9][10][11][12][13][14][15][16][17][18] . Ciprofloxacin (Figure 1), a commonly used broadspectrum fluoroquinolone antibiotic, has shown anticancer activity in several cancer cell lines 19,20 .…”
Section: Introductionmentioning
confidence: 99%